Knowledge of Pregnant Women on Mother-to-Child Transmission of HIV in Meket District, Northeast Ethiopia. (9th February 2015) - Birhane, Tesfaye; Assefa Tessema, Gizachew; Addis Alene, Kefyalew; Dadi, Abel Fekadu
Abstract : Knowledge of pregnant women on the three periods of mother-to-child transmission (MTCT) of HIV has implication for child HIV acquisition. This study aims to assess the knowledge of pregnant women on mother-to-child transmission of HIV and to identify associated factors in Meket district, northeast Ethiopia. Logistic regression models were fitted to identify associated factors. Adjusted odds ratios (AOR) with 95% confidence intervals (CI) were used to determine the presence and strength of association. About one-fifth (19%) of women were knowledgeable on mother-to-child transmission of HIV (95% CI: 15.5%, 22.4%). Being urban resident (AOR: 2.69, 95% CI: 1.48, 4.87), having primary education (AOR: 2.41, 95% CI: 1.03, 5.60), reporting receiving information on HIV from health care providers (AOR: 3.24, 95% CI: 1.53, 6.83), having discussion with partner about mother-to-child transmission of HIV (AOR: 2.64, 95% CI: 1.59, 4.39), and attending antenatal care (AOR: 5.80, 95% CI: 2.63, 12.77) were positively associated with increased maternal knowledge of mother-to-child transmission of HIV. Knowledge of mother-to-child transmission of HIV among pregnant women was low. Providing information, especially for rural women and their partners, is highly recommended.